Flight behavior : a novel - Kingsolver, Barbara (Harper, 2012)
Tired of living on a failing farm and suffering oppressive poverty, bored housewife Dellarobia Turnbow, on the way to meet a potential lover, is detoured by a miraculous event on the Appalachian mountainside that ignites a media and religious firestorm that changes her life forever.